Trick of Political Identity: Analysing Appraisal System on 212 Movement Reunion in Online Media - Fahmi Gunawan; Yopi Thahara; Faizal Risdianto (Register Journal, 2019)
This study aims to evaluate the appraisal system of the 212 movement reunion in online media. Data were from the news of  “trick of political identity” in Tirto online media. Data analysis was conducted using Spradley's theory modified by Santosa. The results indicate that appraisal system pattern of 212 reunion movement utilize attitude (43%), graduation (15%) and engagement system (42%). The attitude system uses a 42% affective subsystem pattern and 58% subsystem judgment. Graduation system uses a 70% force and 30% focus pattern. The engagement system is dominated by the use of heterogloss patterns of 82% rather than 18% monoglos. This percentage shows that the author discusses political identity in the 212 movement reunion. In his writing, the author is objective, neutral, independent and adheres to the principle of professionalism. This is proven by the high percentage of subsystem judgment 58% on the attitude system and 82% heterogloss usage on engagement system. The high percentage of use of focus force patterns shows that the author tries to use language that is easily understood by the wider community Keywords: Media online; Political Identity; 212 Movement Reunion; Appraisal System.